Populists and fiscal policy: The case of Poland - Maciej Wysocki; Cezary Wójcik; Andreas Freytag (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2022)
The past decade has witnessed an increase in populist movements across the world. Some of those movements have gained strong political support and formed populist governments promising new sets of economic and fiscal policies. This raises the pertinent policy question: how do such populist governments influence fiscal policy outcomes? We approach this question by looking at the case of Poland which according to several recent studies has experienced the highest level of populist rhetorics in recent years. Indeed, when the new populist government took power, between 2015-2019, Poland experienced a major social and fiscal policy shifts: the new government decreased the statutory retirement age despite sever aging problem and launched one of the biggest social programs in Europe which resulted in sharp increase in political support for the government. In the paper we provide some first evidence of the impact of such policies on fiscal outcomes. Our analysis reveals that fiscal sustainability parameters have significantly deteriorated sharply after 2015 when the new government undertook populist policies, despite the fact that current (observable) deficit and debt levels remained stable. Specifically, our estimates suggest that just after a year since the introduction of the new fiscal program, the strength of reaction of the primary balance to a change of the public debt decreased by nearly 50% in 2017 and the parameter turned negative and statistically insignificant thereafter which means that from 2018 fiscal policy lacked long-term sustainability. Overall, our estimations show that in the period of 2016-2019 fiscal sustainability parameters were the lowest since Poland joined the EU in 2004. While our analysis has several limitations, the case of the populist government in Poland provides some early evidence that populists do have negative impact on long-term fiscal sustainability.
Keywords: C22; E60; H63; 330; fiscal sustainability; fiscal and social policy; populism